Comparison of quantitative multiple-breath specific ventilation imaging using colocalized 2D oxygen-enhanced MRI and hyperpolarized (3)He MRI - Arai, Tatsuya J. (J Appl Physiol (1985), 2018)
Two magnetic resonance specific ventilation imaging (SVI) techniques, namely, oxygen-enhanced proton (OE-(1)H) and hyperpolarized (3)He (HP-(3)He), were compared in eight healthy supine subjects [age 32 (6) yr]. An in-house radio frequency coil array for (1)H configured with the (3)He transmit-receive coil in situ enabled acquisition of SVI data from two nuclei from the same slice without repositioning the subjects. After 3 × 3 voxel downsampling to account for spatial registration errors between the two SV images, the voxel-by-voxel correlation coefficient of two SV maps ranged from 0.11 to 0.63 [0.46 mean (0.17 SD); P < 0.05]. Several indexes were analyzed and compared from the tidal volume-matched SV maps: the mean of SV log-normal distribution (SVmean), the standard deviation of the distribution as a measure of SV heterogeneity (SVwidth), and the gravitational gradient (SVslope). There were no significant differences in SVmean [OE-(1)H: 0.28 (0.08) and HP-(3)He: 0.32 (0.14)], SVwidths [OE-(1)H: 0.28 (0.08) and HP-(3)He: 0.27 (0.10)], and SVslopes [OE-(1)H: −0.016 (0.006) cm(−1) and HP-(3)He: −0.013 (0.007) cm(−1)]. Despite the statistical similarities of the population averages, Bland-Altman analysis demonstrated large individual intertechnique variability. SDs of differences in these indexes were 42% (SVmean), 46% (SVwidths), and 62% (SVslopes) of their corresponding overall mean values. The present study showed that two independent, spatially coregistered, SVI techniques presented a moderate positive voxel-by-voxel correlation. Population averages of SVmean, SVwidth, and SVslope were in close agreement. However, the lack of agreement when the data sets were analyzed individually might indicate some fundamental mechanistic differences between the techniques. NEW & NOTEWORTHY To the best of our knowledge, this is the first cross-comparison of two different specific ventilation (SV) MRI techniques in the human lung (i.e., oxygen-enhanced proton and hyperpolarized (3)He). The present study showed that two types of spatially coregistered SV images presented a modest positive correlation. The two techniques also yielded similar population averages of SV indexes such as log-normal mean, SV heterogeneity, and the gravitational slope, albeit with some intersubject variability.